(Dis)enfranchised citizens: informational messaging and Puerto Rican political mobilization. (20th October 2021) - Raychaudhuri, Tanika; Proctor, Andrew
ABSTRACT: Puerto Ricans are a growing population on the U.S. mainland. They hold a distinctive position in the hierarchy of American citizenship because they are disenfranchised in national elections on the island but immediately become eligible to vote if they move to the mainland. How can Puerto Ricans on the U.S. mainland be mobilized to participate in politics? This paper explores whether campaign contact increases Puerto Rican political participation. Using observational data, we establish that campaign contact is associated with political participation among mainland Puerto Ricans. We also conduct a survey experiment, testing the mobilizing effects of positive and negative campaign messages that prime Puerto Ricans to think about their group's distinctive political experiences. These messages convey the enfranchised status of Puerto Ricans on the U.S. mainland and their disenfranchised status on the island. While the negative treatment has limited effects, the positive treatment increases intentions to vote, to participate in non-electoral political activities, and feelings of political efficacy relative to a pure control. We observe heterogenous treatment effects across electoral contexts and levels of linked fate with other Puerto Ricans.